ChemInform Abstract: TEMPO‐Mediated Oxidation of Primary Alcohols to Aldehydes under Visible Light and Air. Issue 29 (22nd July 2014) - Liu, Dongwang; Zhou, Hongxia; Gu, Xiangyong; Shen, Xiaoqin; Li, Pixu
Abstract In some cases, the carboxylic acid is also obtained in 1‐20% yield (HPLC).